The Importance Of Learning Strategies In Supporting Children'S Achievement In PAUD Institutions - Fitriana Sari Harahap; Ismaniar Ismaniar (Universitas Negeri Padang, 2022)
The background of the article is that there are still many child development efforts that are not optimal in PAUD institutions. This is thought to be due to many factors, one of which is thought to be because the learning strategies used by educators are not appropriate. This study aims to reveal the importance of learning strategies in supporting children's achievement in PAUD institutions. This article was prepared using a descriptive method with a literature study approach. Sources of data for this research come from books, journals, mass media and online media that are relevant to the research. The results showed; 1) learning strategies greatly influence children's learning activities, 2) each child has different characteristics and different learning strategies as well, and 3) appropriate learning strategies for children can support children's achievement in PAUD institutions.Keywords: learning, support, children's achievement.